Planning for Pandemics: Lessons From the Past Decade - Bennett, Belinda (J Bioeth Inq, 2014)
It is now 10 years since the disease we now know as SARS—severe acute respiratory syndrome—caused more than 700 deaths around the world and made more than 8,000 people ill. More recently, in 2009 the global community experienced the first influenza pandemic of the 21st century—the 2009 H1N1 influenza pandemic. This paper analyses the major developments in international public health law relating to infectious diseases in the period since SARS and considers their implications for pandemic planning.